Potret Strategi Pengawas Sekolah dalam Meningkatkan Mutu Pembelajaran pada Masa Covid-19 - Safrino, Anggani; Muspawi, Mohamad; Musyaiyadah, Musyaiyadah (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2022)
The purpose of the study was to determine the role of school supervisors in improving the quality of learning at SMP Negeri 1 Muaro Jambi during the Covid-19 pandemic. This study used qualitative methods with the type of research case study. The research subjects were the school supervisor, the principal, and five teachers of SMP Negeri 1 Muaro Jambi. The technique of collecting data is using the interview method. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results showed that the supervisor's strategies in improving the quality of learning during the Covid-19 pandemic were: 1) monitoring learning activities, 2) coaching and training, 3) and assessing teacher performance both classically and personally. Based on this research, it is recommended that school supervisors come to school more often to carry out monitoring, guidance and assessment of teachers according to the minister's instructions. The results from supervision can be evaluated and followed up to improve the teacher's ability to carry out teaching and learning during the Covid-19 pandemic.